Coupling of island tourism carbon emission and sustainable resource development – taking Hainan Fenjie Island as an example - Liping Zhu; Yadong Zhou (International Journal of Sustainable Energy, 2023)
ABSTRACTFenjie Island, as an isolated island, has evolved into a 5A-rated tourist destination. However, in recent years, due to the one-sided pursuit of economic gains, the island has continuously developed its tourism resources, resulting in over-exploitation of resources and significant ecological impacts. This study meticulously scrutinizes tourism-related carbon emissions in comparison to the island's natural capacities. Comprehensive research spans ships, accommodations, dining, and various activities, revealing emissions surpassing nature's limits. The study delves into intricate emission models, emphasizing energy-intensive sectors.Empirical findings underscore a pressing disparity: daily emissions far exceed the island's absorption and purification capacities, underscoring the urgency for intervention. To restore equilibrium, the study proposes recalibrating tourism by aligning it with the island's natural resources. Forest and seawater capacities emerge as vital benchmarks for sustainable tourist numbers. Proposed strategies emphasize rigorous energy conservation and emissions reduction, offering a roadmap for sustainable development.These robust findings provide an essential scientific basis for Fenjie Island's future. They illuminate a path toward balanced growth, crucial for harmonizing economic prosperity and environmental preservation. Informed by this research, policymakers can steer the island's trajectory, ensuring a sustainable, thriving future amidst the challenges of modern tourism..